Analisis Perwatakan Dan Nilai-Nilai Psikologi Tokoh Utama Dalam Novel “The Silent Patient” Karya Alex Michaelides Sebagai Alternatif Bahan Ajar Mengulas Novel Kelas XII SMK - Agil Purnama; Dheni Harmaen; Rendy Triandy (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is motivated by the author's desire to introduce novel literature to students and explore everything in it in the form of content, language, elements, rules, and genres in the novel. This study aims to analyze the character traits of the main character in the novel The Silent Patient by Alex Michaelides and to analyze the psychological values ​​of the main character by using Sigmund Freud's personality theory, namely id, ego, and super ego. This research is also an alternative teaching material regarding the content and language of novels for class XII students of SMA and SMK. The method used in this research is descriptive qualitative. The data source used in this research is the literary novel entitled The Silent Patient written by Alex Michaelides. The research data obtained is in the form of the results of the analysis of the character of the main character who has two character traits, namely the protagonist and antagonist. As well as the main characters who have psychological values ​​in accordance with Sigmund Freud's personality theory, namely the id, ego, and super ego. The results of the analysis from this study were then adjusted to the demands of the curriculum, namely referring to Core Competence and Basic Competence 3.9 regarding the content and language of the novel. Then made a teaching material to support the learning process of class XII students. The content and language teaching materials of the novel are based on the research process that has been carried out, and can be used in Indonesian language subjects.